The impact of poor glycemic control on lipid profile variables in children with type 1 diabetes mellitus - Neda Mostofizadeh; Mahin Hashemipour; Marjan Roostazadeh; Elham Hashemi-Dehkordi; Armindokht Shahsanai; Mohsen Reisi (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Type 1 diabetes mellitus (T1DM) and its related comorbidities are considered an important health issue. This study aimed to evaluate the impact of glycemic control on lipid profile variables in children with T1DM. MATERIALS AND METHODS: This study included 274 children (≤19 years of age) with T1DM who had referred to the outpatient clinics of endocrinology in Emam-Hossein Hospital of Isfahan, Iran. Based on American Diabetes Association criteria, patients were divided into two groups including optimal glycemic control (OGC) and poor glycemic control (PGC). Mean lipid level and frequencies of lipid profile abnormalities between the two studied groups were compared. RESULTS: Mean age of the studied population was 13 ± 5.9 years and 133 (48.5%) were boys. A total of 162 (59.1%) and 112 (40.9%) patients had PGC and OGC, respectively. Hypercholesterolemia was the most common dyslipidemia in both groups (33 [29.1%] of OGC and 63 [39.1%] of PGC patients). The frequency of high low-density lipoprotein (LDL) was significantly higher in patients with PGC than those with OCG (P = 0.007). The frequencies of hypercholesterolemia, hypertriglyceridemia, and low levels of high-density lipoprotein were also higher in PGC group, but did not reach the significant threshold. CONCLUSION: It is suggested that glycemic control is in association with lipid profile abnormality in patients with T1DM. High LDL was significantly more frequent in patients with PGC than those with OGC. It is recommended to investigate the role of glycemic control on other cardiometabolic risk factors of T1DM patients. Our findings could be used for planning preventative strategies for reducing T1DM-related cardiovascular disease.